A programmed text in statistics - 444477 Hine, J.; Wetherill, G. Barrie (London : Chapman and Hall, 1975)
Vol.1. Summarizing data -- v.2. Basic theory -- v.3. The t-test and X2 goodness of fit -- v.4. Tests on variance and regression